1992
DOI: 10.1577/1548-8659(1992)121<0192:poneto>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Nine External Tags on Hatchery-Reared Rainbow Trout

Abstract: We evaluated nine commercially available tags to determine their suitability for marking yearling rainbow trout Oncorhynchus mykiss reared in raceways and circular tanks. The tags tested were Floy vinyl tubing tags FD‐67 anchor, FT‐2 dart, FT‐4 cinch‐up, and FT‐4 lock‐on; modified Carlin; modified Petersen disk; Monel strap 4‐1005; Monel butt end 4‐1242; and Stoffel fish seal. After 9 months, tag losses from raceway fish were lowest (8%) for the FT‐4 lock‐on tag; in tanks, none of the FT‐2 dart, FT‐4 cinch‐up,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
4
1

Year Published

1997
1997
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(26 citation statements)
references
References 0 publications
0
21
4
1
Order By: Relevance
“…These include external tags (McAllister et al 1992), in addition to advanced electronic, transponder and radio-based systems (Cookingham & Ruetz 2008, Campana et al 2009, Shroyer & Logsdon 2009). In terrestrial agriculture, physical tags, usually placed in the animal's ear soon after birth, are used widely for documenting both ownership and animal pedigree.…”
Section: Review Of the Dna Stand-by Methodsmentioning
confidence: 99%
“…These include external tags (McAllister et al 1992), in addition to advanced electronic, transponder and radio-based systems (Cookingham & Ruetz 2008, Campana et al 2009, Shroyer & Logsdon 2009). In terrestrial agriculture, physical tags, usually placed in the animal's ear soon after birth, are used widely for documenting both ownership and animal pedigree.…”
Section: Review Of the Dna Stand-by Methodsmentioning
confidence: 99%
“…For example, tag loss rates in rainbow trout were 12–19% for FD‐67 anchor (similar to the anchor T‐tag) and 13–32% for Carlin tags over a 9‐ to 12‐month period in a hatchery environment (McAllister et al . ). Similarly, the overall loss rate of surgically implanted radio transmitter in rainbow trout was observed to be 13% within 12 weeks (Welch et al .…”
Section: Discussionmentioning
confidence: 97%
“…Whereas, many earlier studies of retention rates of the different types of anchor tag, Carlin tags, or surgically implanted radio transmitters reported higher tag loss rates than those in the present experiment (McAllister et al . ; Lacroix et al . ; Welch et al .…”
Section: Discussionmentioning
confidence: 99%
“…Squid that showed any visible damage, primarily from cannibalistic attacks by other squid, were not tagged. McAllister et al (1992) evaluated 9 commercially available tags to determine their suitability for marking rainbow trout Onchorhynchus mykiss and found that the tubing tags (model FT-4 cinch-up, Floy Tag) were the most effective tag for fish maintained in raceways. The spaghetti-type, plastic cinch-up tag also showed high performance when it was used to insert intraperitoneal transmitters into 4 fish species (Butler et al 2009).…”
Section: Field Workmentioning
confidence: 99%